Elegant Beast - Shindô, Kaneto 1912-2012; Munekawa, Nobuo 1918-2005; Wakao, Ayako 1933-; Itō, Yūnosuke 1919-1980; Yamaoka, Hisano 1926-1999 (Radiance, 2024)
A greedy, materialistic family attempts to cover-up the embezzlement committed by the son while keeping their other schemes active. They discover there are other, equally conniving players involved. [www.imdb.de]